Faqīr bastī meṉ thā - Nāṭịq, ʿAlī Akbar (Maiṭarlink Pablišarz, 2023)
On the life and works of Muḥammad Ḥusain Āzād, approximately 1834-1910, Urdu poet.
Der Paralleltitel ist eine Umschrift von der Rückseite der Haupttitelseite
Keywords: Āzād; Muḥammad Ḥusain; approximately 1834-1910.; Poets; Urdu; 19th century; Biography.